Effect of Different Organic Amendments on Growth, Yield and Quality of Broccoli (Brassica oleracea var. italica) - Rajkumari Asha Devi; Rupmalin Kropi; Avinash Kumar; Tanuj Thakur; Ankita (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
To study the effect of different organic amendments on growth, yield and quality of broccoli a field experiment was conducted during 2021–2022 in the Agriculture Research Farm, Lovely Professional University, Punjab A Factorial Randomized Block Design (FRBD) with two factors was used. Factors 1 and 2 are varieties (V1: Palam Vichitra and V2: Palam Kanchan) and biofertilizers (T1: Phosphate Solubilizing Bacteria @ 2 % + Azotobacter @ 2 %, T2: Phosphate solubilizing @ 2 %, T3: Azotobacter @ 2 %, and T0: Control). A total of eight treatments were used, i.e., T1V1 (Palam Vichitra X Phosphate Solubilizing Bacteria @ 2 % + Azotobacter @ 2 %), T2V1 (Palam Vichitra X P.S.B @ 2 %), T3V1 (Palam Vichitra X Azotobacter @ 2 %), T0V1 (Palam Vichitra X Control), T1V1 (Palam Vichitra X Phosphate Solubilizing Bacteria @ 2% + Azotobacter @ 2 %), T0V1 (Palam Kanchan X Phosphate solubilizing bacteria @ 2 %), T3V2 (Palam Kanchan X Azotobacter @ 2 %), T0V2 (Palam Kanchan X Control). The experiment reveals that among all treatments like growth, quality and yield parameters T1 showed the best result for V1 and in V2, T3 showed the best result for almost all the parameters. Floral bud initiation was early when treated with T1 in both the varieties, i.e., V1 (63 DAT) and V2 (63.67 DAT). Days to harvest were the same for all the treatments in V1 (90 DAT) and in V2, T1 (90 DAT) took the least amount of time for harvesting. It can be concluded that, combination of Azotobacter @ 2 % with other organic amendments and treatment T1 give higher yield and better quality of broccoli.